Effect of fruit and host fly species on the associative learning by Fopius arisanus - Monsia, A.; Mègnigbèto, G.S.B.; Gnanvossou, D.; Karlsson, M.F. (Cambridge University Press, 2019)
Parasitoids, released in augmentative biological control programmes, which display a rapid host-location capacity, have a higher likelihood of successfully controlling target pest species. By learning to associate sensory cues to a suitable oviposition site, might parasitoids used as biological control agents, locate hosts more rapidly, and perhaps increase the efficacity of e.g. Tephritidae fruit fly management. We studied associative learning of Fopius arisanus (Hymenoptera: Braconidae) and tested its range of learning in natural and conditional hosts and host fruits, i.e. Bactrocera dorsalis, Zeugodacus cucurbitae, Ceratitis capitata and Ceratitis cosyra (Diptera: Tephritidae) and on fruits (papaya, tomato, banana). Naïve female F. arisanus were compared with experienced wasps, which had been offered infested and non-infested fruit, and been allowed to oviposit. Preferences for olfactory cues from infested fruits were thereafter assessed in a two-choice olfactometer. Naïve and trained parasitoids preference differed in general and non-responders to infested fruits were higher among naïve parasitoids. The trained wasps preferred the fruit infested in the training more than the control fruit, for all combination, except when C. cosyra infested the fruits, hence avoidance behavioural response was observed towards the odour of the infested fruit. Fopius arisanus was capable of behaviourally respond to the learned information, e.g. associative odour learning was achieved, yet limited depending on interaction level, fruit fly and fruit combination. To create F. arisanus preference of an associated odour, it might hence be needed to ensure oviposition in perceived suitable host and host fruit, for the parasitoid learning to become favourable in a biological control setup.